The Effectiveness Test of Using Various Planting Media by Giving Coconut Water as Nutrient to the Growth of Microgreen Sunflower Plants (Helianthus annuus L.) - Ade Fipriani Lubis; Armaniar Armaniar; Dian Handayani (Jurnal Penelitian Pendidikan IPA, 2023)
The research was conducted at the Tissue Culture Laboratory, Faculty of Agriculture, University of Asahan, from December 2022 to January 2023. This study aims to determine the effectiveness of planting media and coconut water on the growth of microgreen sunflower plants. The design used is a factorial Randomised Complete Design (CRD), with 2 treatment factors, the first factor is: Planting Media (M), consisting of soil (M0), cocopeat (M1), rockwool (M2), husk charcoal (M3). The second factor is: Coconut Water (K), consisting of (K0) 0%, (K1) 25%, (K2) 50%, (K3) 75%, (K4) 100%. Observed variables: seed germination potential, number of seed germination and chlorophyll rf (retention/retardation factor) value. The results showed that the planting media had a very significant effect on all observed parameters. Giving coconut water has a very significant effect on chlorophyll rf. There is an interaction between planting media and coconut water on chlorophyll rf.